Англоязычные заимствования в составе сложных немецких слов - Крайнова, О.С.; Исаев, Э.Ш. (Культура народов Причерноморья, 2014)
У статті наведено результати дослідження складних німецьких слів, до структури яких
входять англіцизми. Проведено структурно-словотворчий аналіз, було надано детальне визначення
поняття запозичення, визначені шляхи та причини запозичення англіцизмов, розглянуто асиміляцію
англіцизмів.
В ході дослідження були використані наступні методи: метод суцільної вибірки при роботі з
друкарськими джерелами; метод аналізу відібраного матеріалу; метод структурного аналізу зібраного
матеріалу; метод словотворчого аналізу. Наукова новизна роботи полягає в комплексному описі
особливостей функціонування англіцизмов у структурі складних німецьких слів; у виявленні і описі
процесів їх засвоєння. В статье приведены результаты исследования сложных немецких слов, в состав которых
входят англицизмы. Проведен структурно-словообразовательный анализ англоязычных заимствований,
было дано подробное определение понятия заимствования, определены пути, причины заимствования,
рассмотрена ассимиляция англицизмов.
В ходе исследования были использованы следующие методы: метод сплошной выборки при работе с
печатными источниками; метод анализа отобранного материала; метод структурного анализа
собранного материала; метод словообразовательного анализа. Научная новизна работы заключается в
комплексном описании особенностей функционирования англоязычных заимствованных слов в составе
сложных немецких слов; в выявлении и описании их освоения; в описании и анализе методов образования
сложных немецких слов, в состав которых входят англицизмы. In the research paper are given results of research of compound German words which structure
includes anglicisms. It was carried out structural-word-formative analysis of English-speaking loan-words as a
part of compound German words. It was given detailed definitions of concept of borrowing, ways, the reasons of
loan were studied and defined. Also assimilation of anglicisms in German was considered. Results were
systematized and conclusions were drawn.
During research were used the following methods: method of continuous sample; method of the analysis of the
selected material; method of the structural analysis; method of the word-formation analysis.
Scientific novelty of paper consists in the complex description of features of functioning of English loan-words as
a part of compound German words; in identification and description of their phonetic-graphic, morphological
and semantic assimilation; in the description and the analysis of methods of formation of compound German
words which structure includes borrowings.
Currency of paper is defined by increase of influence of English on German for the last decade as it is used in
many spheres of public and scientific life, in particular in mass media. Articles contain a huge number of
English-speaking borrowings because English, which has become at the end of the 20th century leading means
of the international communication, storages and information transfers, has considerable influence on German.
The problem of borrowings is important and topicall because in the last decades were created favorable
conditions for loan by German of foreign-language lexicon. Every day in newspapers and magazines it is
possible to face words and the expressions which have come to German from English.